California State University, East Bay 2014 Women's Volleyball schedule card - California State University, East Bay Athletics Department:::::: (2014)
Schedule card listing dates, opponents, locations, and times of women's volleyball matches in 2014. Ashia Joseph is pictured on the front of the card, and the card appears to be signed by her.